2015
DOI: 10.3390/rs70505951
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sowing Date on Yield and Water Use Efficiency of Wheat Analyzed through Spatial Modeling and FORMOSAT-2 Images

Abstract: Regional analysis of water use efficiency (WUE) is a relevant method for diagnosing the performance of irrigation systems in water-limited environments. In this study, we investigated the potential of FORMOSAT-2 images to provide spatial estimates of WUE over irrigated wheat crops cultivated within the semi-arid Yaqui Valley, in the northwest of Mexico. FORMOSAT-2 provided us with a unique dataset of 36 images at a high resolution (8 m) encompassing the wheat growing season from November 2007 to May 2008. Time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 75 publications
(108 reference statements)
2
37
0
1
Order By: Relevance
“…This underestimation corresponds to a global overestimation of the ETa (Table 3). This finding is in agreement with what has been reported by Duchemin et al [29], who observed a 20% error in ETa model simulation compared to the measurements by eddy covariance. The overestimation of water demands provide false information to decision maker for more irrigation than actually needed.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This underestimation corresponds to a global overestimation of the ETa (Table 3). This finding is in agreement with what has been reported by Duchemin et al [29], who observed a 20% error in ETa model simulation compared to the measurements by eddy covariance. The overestimation of water demands provide false information to decision maker for more irrigation than actually needed.…”
Section: Discussionsupporting
confidence: 93%
“…The SAFYE model, developed by Duchemin, et al [29] and Battude, et al [30], was used in this study. This model couples the original SAFY crop growth model [25] with the FAO-56 soil water budget model [31] to simulate crop growth and soil moisture at a daily step, including LAI, aboveground biomass, grain yield, crop transpiration, and soil water content.…”
Section: The Safye Modelmentioning
confidence: 99%
“…Meanwhile, the yield of different water deficit scenarios in the late growth stage was hard to differentiate due to similar LAI and dry matter. To overcome this weakness of the model, Duchemin et al (2015) proposed to add a stress factor to response the effect of soil water deficit to crop development by integrating water budget (Allen et al, 1998) into the SAFY model. Moreover, the dynamic positive and negative effects of HI generated by some functions or modules related to water and heat stress could improve adaptability and accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…All of the stresses induced by water, nutrient, salinity, etc., are assumed to be integrated in a parameter of effective light use efficiency (ELUE). To date, the SAFY model has been verified on several crops such as corn (Claverie et al, 2012; Battude et al, 2016) and wheat (Fieuzal et al, 2011; Duchemin et al, 2015; Dong et al, 2016) under different climatic conditions. Claverie et al (2012) used the model to estimate sunflower yield with good accuracy ( r = 0.97, p < 0.03).…”
mentioning
confidence: 99%
“…The same modification had been formerly proposed by [47,48], introducing a dependence of biomass yield on crop water stress. This modification was made since it allows an explicit assessment of the crop response to water availability and the characterization of water stress, which is lacking in the original model.…”
Section: Crop Growth Simulation Modelsmentioning
confidence: 90%